Faktor-Faktor Yang Mempengaruhi Konsumsi Rumah Tangga di Kelurahan Sungai Andai Kota Banjarmasin - Sasmilika Rezky, Naureen; Chandriyanti, Ika (PPJP ULM, 2024)
This research was conducted to provide answers to the results of an analysis of the influence of income, age, and number of dependents on household consumption which is located in Sungai Andai Village, Banjarmasin City. Taking a sample of 100 household heads through a simple random sampling technique, using primary data quantitative research with multiple linear regression method. Based on the results that have been obtained, income, age and number of dependents have a significant influence jointly/simultaneously and individually/partially. The income variable is the most dominant factor compared to other variables that affect household consumption in the Sungai Andai Village, Banjarmasin City.